A novel pathogenic RHOA variant in a patient with patterned cutaneous hypopigmentation associated with extracutaneous findings. Issue 2 (17th February 2022) - Cai, Zhuo Ran; McCuaig, Catherine; Hatami, Afshin; Rivière, Jean‐Baptiste; Marcoux, Danielle
Abstract: RHOA ‐related neuroectodermal syndrome is characterised by linear skin hypopigmentation along Blaschko's lines associated with alopecia, leukoencephalopathy, facial and limb hypoplasia, and ocular, dental, and acral anomalies. Herein, we report a patient with patterned cutaneous hypopigmentation with a similar phenotype due to a novel postzygotic RHOA variant (c.210G>T; p.Arg70Ser). This illustrates that the complexity of the orchestration of morphogenesis and organogenesis can be affected by different variants in the same gene.